2021
DOI: 10.12659/msm.929890
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Ossification After Prestige-LP Cervical Disc Arthroplasty Is Related to Insufficient Sagittal Coverage of the Endplate By the Prosthesis

Abstract: Background Heterotopic ossification (HO) is a major complication after cervical disc arthroplasty (CDR) that has attracted the attention of spine surgeons. There remains a great deal of controversy regarding the surgical risk factors. The present study investigated the correlation between insufficient sagittal coverage of the prosthesis-endplate and HO after CDR and explored strategies to prevent it. Material/Methods We included 73 patients who underwent Prestige-LP art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Although there is still no effective way of reducing the risk T. Takami et al of HO long after ACDR, Xu et al suggested that the occurrence of HO after ACDR may be related to insufficient sagittal coverage of the endplate by CAD. 68) Migration or dislocation of CAD after ACDR is a rare complication but may result in serious problems once it occurs. Previous reports of such complications are limited to case reports.…”
Section: Acdr-specific Complicationsmentioning
confidence: 99%
“…Although there is still no effective way of reducing the risk T. Takami et al of HO long after ACDR, Xu et al suggested that the occurrence of HO after ACDR may be related to insufficient sagittal coverage of the endplate by CAD. 68) Migration or dislocation of CAD after ACDR is a rare complication but may result in serious problems once it occurs. Previous reports of such complications are limited to case reports.…”
Section: Acdr-specific Complicationsmentioning
confidence: 99%
“…Therefore, we conducted subgroup analyses and meta-regression for these parameters. Furthermore, a high degree of ossification before surgery, 34 insufficient endplate coverage of the prosthesis, [35][36][37] intervertebral space height change before and after surgery ≥ 1.8 mm, 35 excessive intervertebral space distraction, 38 and disk space angle change during operation > 5°3 9 may lead to higher incidences of HO. The above patient characteristics and surgical details may vary between studies.…”
Section: Literature Reviewmentioning
confidence: 99%